Agro-Tourism as a Source of Additional Income in Agriculture (Eurasian Journal of History, Geography and Economics, 2023)
The article highlights issues such as agrotourism, places for overnight stays and recreation related to agriculture and its surroundings, positive features of agrotourism are directly related to all the values that the rural environment brings.